Transcranial Magnetic Stimulation for Improving Dysphagia After Stroke: A Meta-Analysis of Randomized Controlled Trials - Xie, Yu-lei; Wang, Shan; Jia, Jia-meng; Xie, Yu-han; Chen, Xin; Qing, Wu; Wang, Yin-xu (Frontiers in Neuroscience, 2022)
BACKGROUND: Rehabilitation of post-stroke dysphagia is an urgent clinical problem, and repetitive transcranial magnetic stimulation (rTMS) has been widely used in the study of post-stroke function. However, there is no reliable evidence-based evidence on the effect of rTMS on post-stroke dysphagia. This review aims to evaluate the effectiveness and safety of rTMS on post-stroke dysphagia. METHODS: English-language literature published before December 20, 2021, were searched in six electronic databases. Identified articles were screened, data were extracted, and the methodological quality of included trials was assessed. Meta-analysis was performed using RevMan 5.3 software. The GRADE method was used to assess the quality of the evidence. RESULTS: A total of 10 studies with 246 patients were included. Meta-analysis showed that rTMS significantly improved overall swallowing function (standardized mean difference [SMD] -0.76, 95% confidence interval (CI) -1.07 to -0.46, p < 0.0001, n = 206; moderate-quality evidence), Penetration Aspiration Scale (PAS) (mean difference [MD] -1.03, 95% CI -1.51 to -0.55, p < 0.0001, n = 161; low-quality evidence) and Barthel index scale (BI) (MD 23.86, 95% CI 12.73 to 34.99, p < 0.0001, n = 136; moderate-quality evidence). Subgroup analyses revealed that (1) rTMS targeting the affected hemisphere and targeting both hemispheres significantly enhanced overall swallowing function and reduced aspiration. (2) Low-frequency rTMS significantly enhanced overall swallowing function and reduced aspiration, and there was no significant difference between high-frequency rTMS and control group in reducing aspiration (p=0.09). (3) There was no statistical difference in the dropout rate (low-quality evidence) and adverse effects (moderate-quality evidence) between the rTMS group and the control group. CONCLUSION: rTMS improved overall swallowing function and activity of daily living ability and reduced aspiration in post-stroke patients with good acceptability and mild adverse effects.